Personal and Moral Responsibility and Its Relation with Moral Flexibility upon Faculty of Secondary Schools (Journal Of Educational and Psychological Researches, 2023)
AbstractThe factor that keeps society from collapsing and regressing to chaos, violence, and lawbreaking is to stick to the human moral principles and criteria of moral behavior that prevent the spread of corruption and crime to the extent that law becomes devoid of activity and loss its dot errant power in front of chaos. The role of moral behavior is to motivate individuals to respect the general laws in dealing with others. Because of the dissemination of odd behavior patterns within our society, the social links are been badly affected and it's urgent for educational institutions to perform their duty in working on spreading awareness about moral values and avoid deviant directions and socially threatening tendencies and clutching to the moral path in social coherence. To achieve the objective of the research, the researcher built two scales, the first one is to asses personal and moral responsibility according to Glasser's theory, which consists of (41) items. The second one consists of (31) items to measure moral flexibility according to the theory of Jonathan Haidt. The researcher used a five-scale measure to asses the sample response. The researcher tested face validity for the two scales by displaying them on a group of experts. Then, the researcher tested the reliability and discrimination power of items and the relationship between each item with the sum. The scales had applied to the sample which consists of (400) male and female teachers from secondary schools. In the light of results, the researcher put forward some recommendations and suggestions.